2017
DOI: 10.1073/pnas.1709207114
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of phosphorylation and protein dynamics during fertilization and meiotic exit in the Xenopus egg

Abstract: Fertilization releases the meiotic arrest and initiates the events that prepare the egg for the ensuing developmental program. Protein degradation and phosphorylation are known to regulate protein activity during this process. However, the full extent of protein loss and phosphoregulation is still unknown. We examined absolute protein and phosphosite dynamics of the fertilization response by mass spectrometry-based proteomics in electroactivated eggs. To do this, we developed an approach for calculating the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 104 publications
3
40
0
Order By: Relevance
“…A simple view would be to separate these functions based on APC/C coactivator, CDC20 for cyclin destruction and CDH1 for resetting cell status. This is supported by a proteomic analysis of meiotic exit in Xenopus eggs which found that wide-spread dephosphorylation was triggered by the degradation of a small number of proteins, typified by the APC/C CDC20 substrates: CCNB1/2, securin and GMNN (Presler et al, 2017). These eggs lack CDH1, therefore typical APC/C CDH1 substrates such as Aurora kinases were, unsurprisingly, stable.…”
Section: Apc/c Fulfils Two Temporally Distinct Roles During Mitotic Exitmentioning
confidence: 88%
See 2 more Smart Citations
“…A simple view would be to separate these functions based on APC/C coactivator, CDC20 for cyclin destruction and CDH1 for resetting cell status. This is supported by a proteomic analysis of meiotic exit in Xenopus eggs which found that wide-spread dephosphorylation was triggered by the degradation of a small number of proteins, typified by the APC/C CDC20 substrates: CCNB1/2, securin and GMNN (Presler et al, 2017). These eggs lack CDH1, therefore typical APC/C CDH1 substrates such as Aurora kinases were, unsurprisingly, stable.…”
Section: Apc/c Fulfils Two Temporally Distinct Roles During Mitotic Exitmentioning
confidence: 88%
“…Global proteomic analysis of meiotic exit in Xenopus eggs, which lack CDH1, showed that proteolysis was limited to a few key rapidly degraded targets such as cyclin B1, B2 and securin and that dephosphorylation proceeded normally in this system (Presler et al, 2017). Additionally, proteasome inhibition, using MG-132, did not alter the rate of dephosphorylation of PPP1CA-pT320 or PRC1-pT481 in HeLa cells following CDK inhibition (Cundell et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A high fractional stoichiometry combined with dynamic regulation is a strong indication that the site is functional in the cellular context studied 1 . It is possible to determine the absolute occupancy or fractional stoichiometry of phosphorylation sites on a large scale by using ratios observed in both the phosphopeptide, its non-phosphorylated counterpart peptide and the respective protein between treatment conditions from SILAC data 22 and TMT-multiplexed data 23,24 .…”
Section: Global Analysis Of Fractional Phosphorylation Site Stoichiommentioning
confidence: 99%
“…further development. Many of these changes require the activity of calcium-dependent kinases and phosphatases (Horner et al, 2006;Mochida & Hunt, 2007;Takeo, Hawley, & Aigaki, 2010;Takeo, Tsuda, Akahori, Matsuo, & Aigaki, 2006), which alter the phosphoproteome of the egg (Guo et al, 2015;Krauchunas, Horner, & Wolfner, 2012;Presler et al, 2017;Roux, Radeke, Goel, Mushegian, & Foltz, 2008;Zhang, Ahmed-Braimah, Goldberg, & Wolfner, 2019;reviewed in Krauchunas & Wolfner, 2013).…”
mentioning
confidence: 99%